2017
DOI: 10.1021/acs.nanolett.7b03721
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Dimensional Manganese Gallium Nitride Surface Structure Showing Ferromagnetism at Room Temperature

Abstract: Practical applications of semiconductor spintronic devices necessitate ferromagnetic behavior at or above room temperature. In this paper, we demonstrate a two-dimensional manganese gallium nitride surface structure (MnGaN-2D) which is atomically thin and shows ferromagnetic domain structure at room temperature as measured by spin-resolved scanning tunneling microscopy and spectroscopy. Application of small magnetic fields proves that the observed magnetic domains follow a hysteretic behavior. Two initially op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Two-dimensional (2D) materials may exhibit distinctly different properties from those of the bulk counterparts due to dimensional confinement. As the Mermin–Wagner theorem postulates, in the absence of a long-range order in 2D spin-rotational invariant systems with short-range exchange interactions, only 2D spin systems with magnetic anisotropy give hope to suppress the freedom of magnetization by opening the spin-wave excitation gap. Recent experimental studies have realized the long-range ferromagnetic (FM) order in a mechanically exfoliated monolayer of CrI 3 and Cr 2 Ge 2 Te 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) materials may exhibit distinctly different properties from those of the bulk counterparts due to dimensional confinement. As the Mermin–Wagner theorem postulates, in the absence of a long-range order in 2D spin-rotational invariant systems with short-range exchange interactions, only 2D spin systems with magnetic anisotropy give hope to suppress the freedom of magnetization by opening the spin-wave excitation gap. Recent experimental studies have realized the long-range ferromagnetic (FM) order in a mechanically exfoliated monolayer of CrI 3 and Cr 2 Ge 2 Te 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel to the immense efforts on devices, there is great interest in discovering 2D magnetic compounds with high magnetic ordering temperatures and different magnetic phases. Room-temperature ferromagnetism has been realized in molecular beam epitaxy (MBE) grown MnSe x monolayer films and mechanically exfoliated thin Fe 3 GeTe 2 flakes under ionic gating . Beyond vdW magnets, other layered non-vdW materials, such as hematene α-Fe 2 O 3 layers, have been successfully exfoliated from their bulk crystals, in which magnetic order at room temperature has been observed .…”
mentioning
confidence: 99%
“…Due to its great potential in significantly increasing the data-processing speed and integration density, spintronics has attracted more and more research attention. To construct practical spintronic devices, the choice of spintronic materials is crucial. So far, a lot of spintronic materials have been studied, such as a half-metal, , which is any substance that acts like a metal in one spin channel and a semiconductor in the other spin channel and can provide completely spin-polarized currents. Recently, d 0 ferromagnetism has attracted great attention. As an example, in 2018, Chakraborty et al found that carbon-doped Y 2 O 3 shows room-temperature d 0 ferromagnetism.…”
Section: Introductionmentioning
confidence: 99%